2011
DOI: 10.1007/s10109-011-0150-z
|View full text |Cite
|
Sign up to set email alerts
|

Industrial agglomeration and transport accessibility in metropolitan Seoul

Abstract: This study aims to reveal the relationship between industrial agglomeration and transport accessibility in the Seoul metropolitan area. Our study suggests that in spite of the rapid expansion of the Seoul metropolitan area, central business districts still function as centers of the industry and transportation system; the agglomeration of most industrial subsectors are occurring in central areas and only primary and manufacturing sectors' clusters are located out of these areas; both of subway and road network… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(36 citation statements)
references
References 38 publications
(35 reference statements)
2
28
0
1
Order By: Relevance
“…Jiwattanakulpaisarn et al (2010) found that increased accessibility is a determinant of state employment growth in the services sector. Song et al (2012) found that accessibility is closely linked to industrial agglomerations in the Seoul metropolitan area. In addition, several authors have analyzed the effect of accessibility on labor supply (see e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Jiwattanakulpaisarn et al (2010) found that increased accessibility is a determinant of state employment growth in the services sector. Song et al (2012) found that accessibility is closely linked to industrial agglomerations in the Seoul metropolitan area. In addition, several authors have analyzed the effect of accessibility on labor supply (see e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Most empirical studies from economic geography have predefined industrial agglomeration based on the authors' knowledge of the region, rather than defining it on a statistical basis (Song, Lee, Anderson, & Lakshmanan, 2012). Such qualitative distinction may work fairly well if industrial agglomerations are identified at a national or international level.…”
Section: Industrial Agglomerationmentioning
confidence: 99%
“…They studied total flow (the sum of arrivals and departures), differential flow, and flow ratio variation in these clusters for a time of day segments. In another study, Song et al identified the type of industrial agglomerations and analyzed each of these orientations with a respect to different transportation modes assess relation with transport accessibility [26]. This study gauged the proximity of agglomerations to different transport modes to access the source of flow and importance of transport accessibility for industry types.…”
Section: Flow Orientationmentioning
confidence: 99%